Respon Tanaman Selada Romaine (Lactuca sativa L.) pada Berbagai Konsentrasi AB Mix dan Bakteri Fotosintetik pada Sistem Hidroponik Rakit Apung - Fajri , Muhamad Nizarul; Yulianti, Nani; Fanani, Muhammad Zainal (Jurnal Pertanian, 2025)
While the demand for vegetables continues to increase every year, lettuce production has not been able to meet the high market demand due to shrinking productivity and available land due to conversion of agricultural land. This study aims to determine the response of romaine lettuce plants to various concentrations of AB mix, photosynthetic bacteria and the interaction between the two with a floating raft hydroponic system. The research design used a two-factorial completely randomized design (CRD). The first factor is the concentration of AB mix nutrients consisting of 5 treatment levels, namely 400 ppm, 600 ppm, 800 ppm, 1000 ppm and 1200 ppm. The second factor is the concentration of photosynthetic bacteria consisting of 3 treatment levels, namely 10 ml/L-1 15 ml L-1 and 20 ml L-1. The results showed that giving the concentration of AB mix nutrients 600 ppm can increase the growth of plant height and giving the concentration of photosynthetic bacteria 10ml L-1 can increase the number of leaves of romaine lettuce plants. Keywords: Nutrition, Lettuce, Productivity, Synechococus sp.